The tenderness of the grotesque in Paula Rego's meeting with Adília Lopes - Souza, Vítor de (2013)
The break with the classical conceptualization of art, questioning the concept of ‘sublime’ - in which there was a lowering of values, from eternity to embodiment - brings us to the grotesque and what is meant by art, beautiful and, consequently, its opposite.?With this article, we intend to find out how the grotesque is spread through the paintings of Paula Rego and the writings of Adília Lopes and if what the painter commented about Adília’s work, and her own artistic productions, using the epithet “grotesque beautiful” and having “a lot of tenderness”, is verifiable. The main postulates on the grotesque were produced by Mikhail Bakhtin, Wolfgang Kayser and Victor Hugo. In addition to the productions of each one of the creators, the crossing of both authors was also observed in the book “Obra”, an anthology of Adília Lopes, with images by Rego.